2021
DOI: 10.1200/jco.2021.39.15_suppl.tps3149
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 and phase 2a, first-in-human (FIH) study, of DRP-104, a broad glutamine antagonist, in adult patients with advanced solid tumors.

Abstract: TPS3149 Background: Dependence of cancer cells on glutamine has made glutaminolysis an attractive therapeutic target in cancer. Prior clinical trials evaluating glutamine analogues for the treatment of cancer were abandoned due to lack of efficacy and/or tolerability. DON (6-Diazo-5-oxo-L-norleucine) is an irreversible inhibitor of several enzymes that utilize glutamine as a metabolic substrate. In addition to direct anti-tumor efficacy, inhibition of glutamine metabolism in the tumor microenvironment has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Interestingly, this observation was unique to ASNS among the known DON target enzymes, as expression of well-studied targets such as GLS and GLS2 did not correlate in this way. Very little is known about what might dictate patient stratification for DON-based prodrugs that are currently in clinical trials 37 . Interestingly, in atypical teratoid/rhabdoid tumors (ATRT), which is a rare and aggressive cancer of the brain and spinal cord in infants, metabolic profiling revealed a unique dependence on glutamine for survival in ATRT cell lines with high MYC expression 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, this observation was unique to ASNS among the known DON target enzymes, as expression of well-studied targets such as GLS and GLS2 did not correlate in this way. Very little is known about what might dictate patient stratification for DON-based prodrugs that are currently in clinical trials 37 . Interestingly, in atypical teratoid/rhabdoid tumors (ATRT), which is a rare and aggressive cancer of the brain and spinal cord in infants, metabolic profiling revealed a unique dependence on glutamine for survival in ATRT cell lines with high MYC expression 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The immune regulation of DRP-104 showed great potential for combined use of DRP-104 with immunotherapy. In 2020, combined DRP-104 with atezolizumab (anti-PD-1) entered the clinical trial (NCT04471415) in the treatment of advanced solid tumors ( Johnson et al, 2021 ). A study has shown that DRP-104 can significantly inhibit the tumor growth of a variety of PDAC models in vivo ( Encarnación-Rosado et al, 2023 ).…”
Section: Drugs Targeting Glutamine Metabolism For Cancer Treatmentmentioning
confidence: 99%
“…[ 80 ] In a first-in-human phase 1/2a, multicenter, multicohort study, the safety, tolerability, and antitumor activity of DRP-104 alone and in combination with atezolizumab, a PD-L1 inhibitor, is being evaluated. [ 81 ]…”
Section: Therapeutic Agents Used In Combination With Icis To Target T...mentioning
confidence: 99%